2015
DOI: 10.1007/s13157-015-0692-9
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Climate Extremes on NDVI (Normalized Difference Vegetation Index) in the Poyang Lake Basin, China

Abstract: Based on long-term NDVI (Normalized Difference Vegetation Index) derived from Global Inventory Modeling and Mapping Study (GIMMS) and daily meteorological observations from 14 stations in the Poyang Lake Basin, this study investigated the relationship between vegetation variation and climatic extremes during 1982-2006. Ten typical indices were adopted to describe climatic extreme, including two precipitation-related and eight temperature-related indices. Correlation analysis shows that monthly averaged NDVI va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…While the investigation of shorter intervals may appear desirable, one has to note that the reaction time of the NDVI to temperature changes can strongly depend on the type of ecosystem and its resilience or vulnerability in L. Baumbach et al: Impact of temperature extremes on NDVI the presence of perturbations (Gonzalez et al, 2010). In this context, NDVI responses to climate extremes can either be instantaneous or show time lags of even up to 1 month (Tan et al, 2015). Bearing this fact in mind, in addition to the practical necessity of this strategy, defining extreme NDVI events upon a temporal resolution of 16 days appears a reasonable trade-off to account for both instantaneous and delayed responses at least to a certain degree.…”
Section: Event Definitions 321 Ndvimentioning
confidence: 99%
“…While the investigation of shorter intervals may appear desirable, one has to note that the reaction time of the NDVI to temperature changes can strongly depend on the type of ecosystem and its resilience or vulnerability in L. Baumbach et al: Impact of temperature extremes on NDVI the presence of perturbations (Gonzalez et al, 2010). In this context, NDVI responses to climate extremes can either be instantaneous or show time lags of even up to 1 month (Tan et al, 2015). Bearing this fact in mind, in addition to the practical necessity of this strategy, defining extreme NDVI events upon a temporal resolution of 16 days appears a reasonable trade-off to account for both instantaneous and delayed responses at least to a certain degree.…”
Section: Event Definitions 321 Ndvimentioning
confidence: 99%
“…It is widely believed that climate change can cause changes in vegetation cover and may eventually lead to increased frequency and severity of regional extreme events (desertification, salinization, dust storms, floods etc.) [2]. Therefore, exploring the intrinsic relationship between the temporal and spatial changes of vegetation cover and climate change can reveal the evolution process of regional environmental conditions and predict the future development trend.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the forest coverage in PYLB increased dramatically since the 1970s. In addition, other studies also demonstrated that the Normalized Difference Vegetation Index (NDVI) in PYLB presented an increasing trend since the 1980s [35,58,59]. Both historical and remote sensing evidence highlight the increase of vegetation coverage in PYLB, which may play an important role in reducing runoff.…”
Section: Potential Factors Influencing the Catchment Properties' Paramentioning
confidence: 95%
“…The topography of the Poyang Lake Basin (PYLB) varies from highly mountainous regions (maximum elevation of 2200 m above sea level) to alluvial plains in lower reaches of the primary water resources [34,35]. Poyang Lake exchanges water with the Yangtze River through a narrow outlet located in Hukou [35], while receiving water from the five sub-drainage basins of Ganjiang River, Fuhe River, Xinjiang River, Raohe River and Xiushui River [36,37]. Headwater of these rivers is located in boundaries of the east, south and west of Jiangxi Province that are surrounded by high mountains.…”
Section: Overview Of the Poyang Lake Basinmentioning
confidence: 99%
See 1 more Smart Citation